PENGARUH KEMIRINGAN JALAN TAMBANG (GRADE) TERHADAP AFCA (ADJUSTMENT FUEL CONSUMPTION ACTUAL) DENGAN PENDEKATAN NILAI COST BENEFIT PADA UNIT PRODUKSI HDCT-785 DI TAMBANG BATUBARA - Laura Puspita Sari (Jurnal Sistem dan Manajemen Industri, 2021)
Fuel requirements have a direct impact on mining activities. The operator's habits influence the amount of fuel used in operating the equipment, the mine road's slope, and the distance predetermined in the mine design planning. Adjustment Fuel Consumption Actual (AFCA) is the fuel cost, which is influenced by the fuel price, distance, and condition of the mining road billed for overburden and coal mining activities carried out by the contractor. The research methodology uses off-site and on-site analysis. Off-site analysis can be carried out the highest 'Fuel Ratio' owned by the machine based on its specifications and operational activities to find out how much fuel consumption is needed to produce the amount of production per hour (liters/bcm). Meanwhile, it needs to be correlated with the mine road's condition, including the slope of the mine road (grade). This study aims to determine the relationship between road grade and fuel consumption by comparing road grade improvement efforts with cost-benefit analysis.